2014
DOI: 10.17816/ecogen12148-61
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and differentiation of siberian stone pine populations at the southern edge in lowland part of West Siberia

Abstract: Background. Siberian Stone pine (Pinus sibirica Du Tour) is one of the major forest-forming species at West Siberia. Climate change and anthropogenic impact lead to reduction of Siberian stone pine forests at the southern limit of distribution in lowland part of the species range. Materials and methods. Five Siberian Stone pine stands from the trailing edge in transit zone between southern taiga and forest-steppe in West Siberia were studied. Genotypes of 104 trees on 25 allozyme loci coding for 15 enzymes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(16 reference statements)
1
0
0
Order By: Relevance
“…The AMOVA results showed that only 2 % of the total genetic variation occurred among populations. Low differentiation among Siberian stone pine populations revealed in this study is in line with previous reports on Siberian stone pine using allozyme and nuclear simple sequence repeat (nSSR) markers (Petrova et al, 2014;Shuvaev and Ibe, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…The AMOVA results showed that only 2 % of the total genetic variation occurred among populations. Low differentiation among Siberian stone pine populations revealed in this study is in line with previous reports on Siberian stone pine using allozyme and nuclear simple sequence repeat (nSSR) markers (Petrova et al, 2014;Shuvaev and Ibe, 2021).…”
Section: Discussionsupporting
confidence: 92%